(untitled) (Ozone Therapy Global Journal, 2012)
In recent years, ozone therapy as an effective therapeutic method has become more developed and well known. Russia and Cuba have recognized it in their legislation; it is regulated in more than 76% of the Autonomous Regions of Spain; and in Italy four Regions have specified the criteria for practicing it, in addition to two favorable court decisions. Ozone therapy is characterized by the simplicity of its application, its great eff ectiveness , good t olerance, and by t he virtual absence of side effect s. This document, based on the latest books and scie ntific articles on the subject, updates the recent fi ndings t hat j ustif y, from the scie ntific point of view, the medical u se o f ozone . F or ma ny years the applic atio n of ozone in medical practi ce was not well accepted due to unfounded ideas about its toxicity in relation to the high concentrations used in industry. As with any healing technique, ozone therapy is dependent on the dosag e. It i s impor tant to understand that in clinical practice th e conc entr ations o f ozone are lower tha n the toxic levels by severa l orders of magnitude . In this concentration r ange, the oz one acts as a t herape utic sub stance and pres ents immunomodulat i ng, anti-inflammato ry, bactericide, antiviral, fungicide, analgesic properties and others. There are an in creasin g number of scientific so cieties and clinical papers, including m eta-analysis studies. At the same time efforts are being reinforced to regularize this medical practice.